DeepRes: a new deep-learning- and aspect-based local resolution method for electron-microscopy maps. (2019) - Ramırez-Aportela, Erney; Mota, Javier; Conesa, Pablo; Carazoa, Jose Maria; Sorzano, Carlos Oscar S.
No abstract available